THE INFLUENCE OF PROBLEM BASED LEARNING MODELS ON STUDENT’S COGNITIVE BIOLOGY LEARNING OUTCOMES AT SMA NEGERI 2 REJANG LEBONG - Reza Wulandari; Apriza Fitriani (Jurnal IPA Terpadu, 2024)
This research aims to determine whether there is an influence of the problem based learning model on students' cognitive biology learning outcomes. This research is a quasi-experiment using a non-randomized research design, controlled pretest-posttest group design. The population was all class X students of SMA Negeri 2 Rejang Lebong. The sample was selected using a simple random sampling technique. The results of the study showed that the average posttest score for the experimental class was 83.75, while for the control class it was 77.29. The Independent Sample Test shows that there is an influence of the Problem Based Learning (PBL) model on students' cognitive biology learning outcomes. The results of the independent samples t-Test (t) were 0.003 because the p value was <0.05, so it was said that there was an influence between the learning outcomes of the experimental class and the control class. Thus it can be concluded that there is an influence of the Problem Based Learning Model on Student Biology Cognitive Learning Outcomes at SMA Negeri 2 Rejang Lebong.